Kinetics and Fluctuations of Electron-Photon Processes in Conductors - Nietbaevna, Orazbaeva Indira (European Journal of Life Safety and Stability (2660-9630), 2024)
This article is about the kinetics and electron-photon processes in conductors and how they act in reality.a